A joint modeling approach for reliability growth planning considering product life cycle cost performance. (July 2020) - Li, Meiyan; Xu, Dong; Li, Zhaojun Steven
Highlights: A joint modeling approach for reliability growth planning to minimize product life cycle cost. Life cycle cost includes the reliability test cost, product release incentive/penalty, and maintenance cost. Optimal product release timing balances product design cost and post-release maintenance cost. Post-release maintenance cost is quantified as a function of the outcomes from reliability growth planning. Abstract: Reliability growth planning methods have been traditionally focusing on the product design stage rather than the product whole life cycle including both product development and deployment stages. A joint modeling approach for reliability growth planning considering product life cycle cost performance is proposed. The product life cycle performance consists of the cost of reliability growth test, early release incentive or late release penalty, and after sales maintenance cost. The product early release incentive or late release penalty is a virtual cost, which quantifies the impact of product release timing on the product life cycle cost assessment. The reliability growth test cost depends on the allocated testing units and times, which consequently determines the reliability level at product release time and the subsequent maintenance cost. The proposed joint modeling approach balances and determines the optimal product release time and reliability growth test resource allocation with the objective of minimizing the product life cycle cost. A numerical example is illustrated to demonstrate the advantages of the proposed method over traditional reliability growth planning approaches.